ANALISIS POLA HUMAN LEKOCYTE ANTIGEN (HLA) KELAS I PADA PENDERITA DEMAM BERDARAH DENGUE POPULASI INDONESIA DI JAWA TIMUR - F.M. Judajana; Paulus Budiono; Indah Nuraini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
The incidence of Dengue Haemorrhagic Fever (DHF) is obvious rapidly increasing and it may have existed previously, and specificfactors precipitating of the diseases can be identified in Indonesia population. These include environmental changes, demographic factors,host immunity, micro organism variant and drug resistance suggesting that infection will continue to emerge, probably increase andemphasizes the urgent need for effective surveillance. The Immunology approach of Dengue Haemorrhagic Fever as emerging diseaseshas been advanced on two major fronts. First, the elucidation of the basic mechanisms associated antigen recognition, elimination,rejection and immunological protection from recurrence. Secondly, to solve the clinical problem (diagnostic, therapeutic and prevention)the application of the knowledge of immunological memory to diseases is used as a tool. Over expressed emerging pathogens such asmolecularly defined mutated antigen; this antigen as a target of specific immune reaction and has been encountered as a danger signal.The current studies have shown that few immune competent cells (activated T cells and B cells) are exposed to antigen. The immuneconsequence of infectious tissue induced Major Histocompatibility Complex (MHC)/Human Leukocyte Antigen (HLA) molecules expressionon antigen presenting cell and have also shown, that an immunological reaction occurs in all organs in response to a number of diseases.However, most infectious diseases express MHC/HLA class II molecules, in order to recognize the new mutated antigen and also expressthe MHC/HLA class I molecules in order to eliminate those antigen. Progress in the genetic dissection of infectious diseases will also comefrom the complementary analysis of the various biological and clinical phenotypes associated with a given infectious agent, stronglysuggesting that host factors play an important role in susceptibility or resistance to infection. In order to know the regulation processbetween different types of pathogen and the host immune system, as well as the regulation factor of the cross talk between the differentcomponents of the immune response in human as the host, it is important to get an understanding of the immune genetic system. Thisresearch work is aimed at the locating and identifying the HLA class I which encode the protein as immune-component to be involvedin the pathogenesis of DHF as a viral infection base on the examination on 20 DHF patients and have already examined the HLA-A, -Bas HLA class I with the DNA typing-PCR. The results analysis with Chi square with Yates‘s Correction and the relative risk (Wolf rule)is HLA-A*11,-A*24 and HLA-B*15,-B*18 has specific association with DHF on Indonesia population in East Java. The evidence of theinfluence of the immune genetics marker to the DHF is provided by the following observations: (1) the level of infection often differsgreatly among infected subjects, (2) some infected subjects do not develop clinical disease, (3) the clinical manifestations of diseaseseverity, time to onset, duration of disease etc, may differ greatly among symptomatic patients. This finding opens the path to developeffective means of immunotherapy and improved the diagnosis for lesions, in order to apply the current strategies for the developing ofimmunodiagnostic, immunotherapy-based treatment through an infected target cell or developed new effective vaccines.